2008
DOI: 10.1007/s11244-008-9093-0
|View full text |Cite
|
Sign up to set email alerts
|

CO Oxidation and Toluene Hydrogenation by Pt/TiO2 Catalysts Prepared from Dendrimer Encapsulated Nanoparticle Precursors

Abstract: Generation 4 hydroxyl terminated polyamidoamine (PAMAM) dendrimer encapsulated nanoparticles (DENs) were examined as precursors for Pt/TiO 2 catalysts. In this preparation method, the dendrimers were initially used to template and stabilize Pt nanoparticles in solution. DENs were then deposited onto titania, and activation conditions for dendrimer thermolysis were examined. The interactions between PAMAM dendrimers and the titania were found to differ from previous reports of dendrimersupport interactions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…[366][367][368][369][370][371][372][373][374][375] For instance, it has recently been shown by using IR absorption spectroscopy that thermal treatment of the dendrimer-encapsulated nanoparticles (DENs) used in the preparation of a Pt/TiO 2 catalyst in oxidizing atmospheres leads to the formation of surface isocyanates bound to the metal. 376 In Fig. 19, we show another example, from our own laboratory, of how IR absorption spectroscopy can be employed to follow the decomposition of the organic matter during catalyst oxidation, in this case of the poly(amidoamine) (PAMAM) dendrimer used to make the Pt DENs dispersed to ultimately produce a Pt/SiO 2 catalyst.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…[366][367][368][369][370][371][372][373][374][375] For instance, it has recently been shown by using IR absorption spectroscopy that thermal treatment of the dendrimer-encapsulated nanoparticles (DENs) used in the preparation of a Pt/TiO 2 catalyst in oxidizing atmospheres leads to the formation of surface isocyanates bound to the metal. 376 In Fig. 19, we show another example, from our own laboratory, of how IR absorption spectroscopy can be employed to follow the decomposition of the organic matter during catalyst oxidation, in this case of the poly(amidoamine) (PAMAM) dendrimer used to make the Pt DENs dispersed to ultimately produce a Pt/SiO 2 catalyst.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…20 Recently, some research studies have revealed that Pt DENs supported on the titania or silica supports could improve the dispersion of Pt NPs and the recoverability of catalysts. [21][22][23] It is well known that mesoporous alumina (MA) is a support with large surface area, uniform pore size and high thermal stability, which is widely employed in catalysis, adsorption, etc. [24][25][26] Pt DENs are deposited on mesoporous alumina, which decreases the sintering of Pt NPs during post-treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The size of the NPs has a direct affect on their catalytic activity, in addition to the known influence of support composition, pretreatment, and other parameters. 19,68,69,117 In the case of titania, TiO 2 supported NPs may be less active because of a strong metal support interaction (SMSI). 68 Because the Rh 1 /Al 2 O 3 (25%)-SiO 2 (75%) catalyst generally underperformed the commercial 0.5% Rh/Al 2 O 3 catalyst for the hydrogenation of naphthalene and quinoline, TEM and XPS were carried out, before hydrogenation, to determine if there was an obvious difference in NP size and oxidation state for this pair of catalysts, and the results are summarized in Table 3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%